Exploring the formation of social entrepreneurship from an ecological perspective: Evidence from South Korea. Issue 3 (1st July 2021) - Cho, Sangmi; Chun, JongSerl; An, Soyoung
Abstract: This study explores the formation of social entrepreneurship from an ecological perspective as developing personal attributes taking into account the dynamic context of external factors. Semi‐structured in‐depth interviews with 22 social entrepreneur trainees are conducted based on the grounded theory. The main finding is that the paradigm of the social entrepreneurship formation is described through close interactions between the purposeful actors and the decisive environments. Especially, the interdisciplinary social‐economic educational program in which individual attributes are developed—that is, social welfare, business administration, and health studies programs—are part of an important process through which social entrepreneurship is formed. Thus, the study suggests that systematically organized social‐economic education programs should serve as intermediaries in connecting individuals and the environment around them.